Arka pamięci? Kilka uwag na marginesie filmów Aleksandra Sokurowa Rosyjska arka i Frankofonia - Pawletko, Beata (Studia Rossica Posnaniensia, 2020)
Alexander Sokurov is considered to be a creator who often attempts to settle with the uncomfortable past, at the same time revealing the mechanisms of the functioning of power and politics, including the policy of remembrance. The Russian Ark (2002) and Francofonia (2015), which divides over a dozen years and which seemingly concern two different countries and situations, are no different in this respect. And yet, using the same motif in them, i.e. the motif of the museum, Sokurov in Francofonia returns to events that he could not, for various reasons, deal with in a prior movie. We mean here the role of museums, “silent” witnesses of history. The evacuation of works of art from the Hermitage and the Louvre during the war is a source of pride and an element of the victorious narrative, but in the case of Hermitage it is impossible not to think about the price that the city and its inhabitants paid during their siege. They could not be evacuated as efficiently as the museum collections. And thus the idea of saving valuable works of the Hermitage will be invariably associated with the inept evacuation of the people of Leningrad. And it must be admitted that this is not the first opportunity when it comes to Sokurov to remind the world of the painful wound inflicted on the city of Neva and its inhabitants, not only by the Germans, but also to ask about the price of survival.